GC-IMS-Based Preliminary Analysis of Volatile Flavor Compounds in Ejiao at Different Processing Stages - Ning Ma; Rui Guan; Rentang Zhao; Yue Geng (Journal of Food Quality)
In order to find out the changes of flavor substances in the processing of Colla corii asini (Ejiao) and provide reference for the flavor and quality control in the production of Ejiao, gas chromatography-ion mobility spectrometry (GC-IMS) was used to analyze the Ejiao products in different processing stages and establish the fingerprint. The differences among these stages were analyzed using multivariate statistical analysis, and the mechanism underlying volatile flavor compound formation was explored by discriminant analysis of Ejiao at different processing stages. The results indicated that Ejiao contains 47 volatile flavor compounds at different processing stages; they mainly include aldehydes, alcohols, esters, ketones, dimethyl disulfide, thiazole, and pyrazines. During Ejiao processing, the formation of these substances is mainly attributable to the Maillard reaction, amino acid or protein-oxidized lipid interaction, lipid oxidation and degradation, and long-chain compound degradation during heating. Principal component analysis results showed that volatile flavor compounds could be used to distinguish different Ejiao processing stages. The current results provide some reference for flavor and quality control of Ejiao products.